Training as a critical component of elephant research and management in Ghana - Ayesu, Samuel; Tetteh-Kumah, Frank; Gyesi, Halima; Baring-Darko, Rebecca (Pachyderm, 2003)
Notes the increasing need for trained people, beyond conservation personnel themselves, to conduct elephant survey and monitoring programmes and then outlines a training programme in line with these needs undertaken by the Eden Conservation Society in Ghana under the initiative of the AfESG Small Grants Programme. The Society organized one month long course for 12 wildlife and forestry students from Kwame Nkrumah Universite: 2 weeks of theory given in Ankasa Conservation Area followed by 2 weeks of field work focused on a survey of elephant in the Dadieso and Disne River Forest Reserves. A table ’Topics covered in the Training Course for Wildlife Managers’ outlines the topics covered, the skills taught and developed, and the emphasis given to aspects of the training topics. ’The course was designed to provide a continental overview of the status of elephants, problems of elephant management and human-elephant conflict, the biology of elephant populations and individuals, and census methods.’ During the fieldwork phase ’the standard transect-line method (Buckland et al. 1993) was used to survey elephants and other animals on 45 1-km transects. Questionnnaries were administered in 14 randonly selected villages within 7 kms of the reserves’. The authors note that it will take some time to fully evaluate the results of the training, but they list several benefits already evident over the five months subsequent to the course including: the participants increased capability to plan/develop, execute, and report on projects undertaken since the training; their increased understanding of analytical skills; and, the confidence to work as a fully participating member of a research team on other programmes. (Ayesu. 2003)